PENGARUH LINGKUNGAN KERJA, DISIPLIN KERJA, PELATIHAN TERHADAP KINERJA GURU DI YAYASAN PENDIDIKAN NURCAHAYA MEDAN - maria, radikah; ginting, kristi endah ndilosa; yunita, mella (JEBIM Prima, 2024)
This research aims to determine the influence of the work environment, work discipline and training on the performance of Nurcahaya School teachers. Technique sampling using a saturated sample technique, with the sample size is 21 teachers. Data collection using questionnaires, then processed and analyzed using descriptive and quantitative analysis. The results of this research show that: 1) Work Environment, Discipline Work and training together have a significant effect on the performance of Nurcahaya School teachers. 2) Work Environment, Work Discipline and Training partial positive and significant effect on Nurcahaya School Teacher Performance.